An exergy-based study on the relationship between costs and environmental impacts in power plants. (1st November 2017) - Lara, Yolanda; Petrakopoulou, Fontina; Morosuk, Tatiana; Boyano, Alicia; Tsatsaronis, George
Abstract: Exergy-based (exergetic, exergoeconomic and exergoenvironmental) analyses, are used for designing, assessing and improving energy conversion systems. In an exergoeconomic analysis, thermodynamic inefficiencies – represented by exergy destruction – are used in combination with investment costs to calculate the "cost-optimal" layout of a plant. Analogously, in an exergoenvironmental analysis, the aim is to minimize the total environmental impact of a plant. Until today exergoeconomic and exergoenvironmental analyses have been used as separate and distinct tools and the improvement of a plant has been considered in terms of the reduction of either costs or environmental impact. To simultaneously decrease the investment costs and the component-related (manufacturing or construction-related) environmental impacts, their relationship with exergy destruction must be studied in parallel. This paper examines the relationship between exergoeconomic and exergoenvironmental data under various plant operating conditions. A combined-cycle power plant is analyzed and options for a simultaneous improvement from the thermodynamic, economic and environmental viewpoints are discussed. Highlights: Novel analysis combining exergoeconomic and exergoenvironmental methods. Simultaneous thermodynamic, economic and environmental improvements of a power plant. In most cases, efficiency improvements decrease costs and environmental impacts. The trends of investment cost and environmental impact functions do not always agree.